Endoscopic Features of Mucous Cap Polyps: A Way to Predict Serrated Polyps - Brian T. Moy; Faripour Forouhar; Chia-Ling Kuo; Thomas J. Devers (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims The aims of the study were to identify whether a mucous-cap predicts the presence of serrated polyps, and to determine whether additional endoscopic findings predict the presence of a sessile serrated adenomas/polyp (SSA/P). Methods We analyzed 147 mucous-capped polyps with corresponding histology, during 2011-2014. Eight endoscopic features (presence of borders, elevation, rim of debris, location in the colon, size ≥10 mm, varicose vessels, nodularity, and alteration in mucosal folds) of mucous-capped polyps were examined to see if they can predict SSA/Ps. Results A total of 86% (n=126) of mucous-capped polyps were from the right sided serrated pathway (right-sided hyperplastic [n=83], SSA/Ps [n=43], traditional serrated adenoma [n=1]), 10% (n=15) were left-sided hyperplastic polyps, and 3% (n=5) were from the adenoma-carcinoma sequence. The presence of a mucous cap combined with varicose vessels was the only significant predictor for SSA/Ps. The other seven characteristics were not found to be statistically significant for SSA/Ps, although location in the colon and the presence of nodularity trended towards significance. Conclusions Our study suggests that mucous-capped polyps have high predictability for being a part of the serrated pathway. Gastroenterologists should be alert for a mucous-capped polyp with varicose veins, as these lesions have a higher risk of SSA/P.